Exploring Approaches to Contextualize Community Resources in Secondary Level Classroom Instruction in Nepal - Bhattarai, Taranath (Rupandehi Campus Journal, 2025)
This study investigates pedagogical approaches for integrating locally available community resources into secondary-level classroom instruction, with a particular focus on contextualizing real-world practices within the study area. It critically examines the strategies, methods, and techniques employed to bridge the gap between formal education and practical, experience-based learning. The research also proposes actionable strategies for incorporating community resources to enhance functional and task-based instructional practices aimed at promoting practical education. Employing a qualitative research design, data were collected through Participatory Rural Appraisal (PRA), classroom observation, and semi-structured interviews. An interpretative paradigm was used for data analysis. The findings reveal a rich availability of community resources that can be effectively utilized to support skill-oriented, task-based learning, both within the specific study context and more broadly.